2009
DOI: 10.1111/j.1365-2842.2009.01955.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐cortical excitability in healthy human subjects after tongue training

Abstract: Training of specific muscles causes plastic changes in corticomotor pathways which may underlie the effect of various clinical rehabilitation procedures. The paired pulse transcranial magnetic stimulation (ppTMS) technique can be used to assess short interval intra-cortical inhibitory (SICI) and intra-cortical facilitatory (ICF) networks. This study examined changes in SICI and ICF in tongue motor cortex after tongue training in 11 healthy volunteers using ppTMS. Paired pulse TMS was applied to the 'hot-spot' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have examined corticomotor control of tongue movements (4, 14). A series of tongue‐training studies performed by our group have revealed training‐induced neuroplasticity in human corticomotor control of the tongue by demonstrating an increase in motor‐evoked potentials produced by transcranial magnetic stimulation, as well as an increase in the motor cortex (MI) tongue representation (14–17). These studies have all used a highly standardized tongue‐protrusion task with a constant target force and timing of the task (rise time (protrude tongue), top delay (hold tongue protrusion force), fall time (retract tongue), and bottom delay (rest)) (14–16, 18, 19).…”
mentioning
confidence: 99%
“…Previous studies have examined corticomotor control of tongue movements (4, 14). A series of tongue‐training studies performed by our group have revealed training‐induced neuroplasticity in human corticomotor control of the tongue by demonstrating an increase in motor‐evoked potentials produced by transcranial magnetic stimulation, as well as an increase in the motor cortex (MI) tongue representation (14–17). These studies have all used a highly standardized tongue‐protrusion task with a constant target force and timing of the task (rise time (protrude tongue), top delay (hold tongue protrusion force), fall time (retract tongue), and bottom delay (rest)) (14–16, 18, 19).…”
mentioning
confidence: 99%
“…TMS applied to the scalp between 8-9 cm lateral and 2-3 cm anterior to the interauricular line produced clear MEP responses with latencies between 6 and 10 ms in the tongue musculature of all the participants (5,24). The motor thresholds ranged between 31 and 56% (45Á9 AE 2Á4%) of maximum magnetic stimulator output for the tongue motor cortex.…”
Section: Resultsmentioning
confidence: 92%
“…It is also evident that peripheral somatosensory input is necessary in acquisition of new oro-facial motor skills (4). In humans, increase in cortical excitability of the tongue motor cortex (MI) has been reported after different tongue training tasks (5)(6)(7)(8)(9) and also following unilateral local anaesthesia (LA) of the tongue (1) and perioral region (10) compared to the first dorsal interosseous muscle (FDI) as a control. Relatively few studies have used transcranial magnetic stimulation (TMS) to examine the control of the tongue musculature (1,5,(11)(12)(13)(14) as well as few studies have attempted to study the modulation of tongue motor evoked potentials (MEPs) (1,5,7,15).…”
Section: Introductionmentioning
confidence: 99%
“…These neuroplastic changes are associated with significantly improved successful task performance. However, training may not be associated with changes in intra-cortical inhibitory or facilitatory networks [118]. Sensory perturbation induced by experimental intraoral noxious stimulation concomitantly prevents both successful tongue-task performance and the increased tongue-MI excitability associated with the task training ( Fig.…”
Section: Face MImentioning
confidence: 99%